Oil Price Fluctuations and Exchange Rate Dynamics in the MENA Region: Evidence from Non-Causality-in- Variance and Asymmetric Non-Causality Tests - Ridha Nouira; Thouraya Hadj Amor; Christophe Rault (Center for Economic Studies and ifo Institute (CESifo), 2018)
The aim of this paper is to investigate the exchange rate consequences of oil-price fluctuations and to test for the dynamics of oil price volatility by examining interactions between oil market and exchange rate in selected MENA countries (Egypt, Jordan, Morocco, Qatar, Saudi Arabia, Tunisia, and UAE). Using daily time series data covering the period from January 1, 2001 to December 29, 2017, we implement the test for asymmetric non-causality of Hatemi-J (2012), the asymmetric generalized impulse response functions of Hatemi-J (2014), and the test for noncausality-in-variance of Hafner and Herwartz (2006) to examine the presence of volatility spillover between oil prices and exchange rates return series. The econometric investigation reveals in particular that i) when prices are rising in Tunisia and Saudi Arabia, oil prices cause change in exchange rates, and ii) there is significant evidence of volatility spillovers from oil markets to exchange rate markets in the selected MENA countries. These findings have important implications both from the investor's and from the policy-maker's perspective.
Keywords: F31; G01; Q43; 330; oil price shocks; exchange rate volatility; asymmetric causality test; asymmetric generalized impulsion functions; causality-in-variance tests; MENA countries